Evaluation of the miscibility of novel cocoa butter equivalents by Raman mapping and multivariate curve resolution–alternating least squares - Castro-Alayo, E.M.; Torrejón-Valqui, L.; Cayo-Colca, I.S.; Cárdenas-Toro, F.P. (MDPI, 2021)
Cocoa butter (CB) is an ingredient traditionally used in the manufacturing of chocolates, but its availability is decreasing due to its scarcity and high cost. For this reason, other vegetable oils, known as cocoa butter equivalents (CBE), are used to replace CB partially or wholly. In the present work, two Peruvian vegetable oils, coconut oil (CNO) and sacha inchi oil (SIO), are proposed as novel CBEs. Confocal Raman microscopy (CRM) was used for the chemical differentiation and polymorphism of these oils with CB based on their Raman spectra. To analyze their miscibility, two types of blends were prepared: CB with CNO, and CB with SIO. Both were prepared at 5 different concentrations (5%, 15%, 25%, 35%, and 45%). Raman mapping was used to obtain the chemical maps of the blends and analyze their miscibility through distribution maps, histograms and relative standard deviation (RSD). These values were obtained with multivariate curve resolution–alternating least squares. The results show that both vegetable oils are miscible with CB at high concentrations: 45% for CNO and 35% for SIO. At low concentrations, their miscibility decreases. This shows that it is possible to consider these vegetable oils as novel CBEs in the manufacturing of chocolates.
Keywords: Miscibility; Raman spectroscopy; Vegetable oil; Ingredient; Chemistry; Analytical Chemistry (journal); Partial least squares regression; Materials science; Chromatography; Food science; Mathematics; Organic chemistry; Polymer; Statistics; Optics; https://purl.org/pe-repo/ocde/ford#1.04.03